2009
DOI: 10.1063/1.3243689
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient tris(8-hydroxyquinoline) aluminum-based organic light-emitting diodes utilized by balanced energy transfer with cosensitizing fluorescent dyes

Abstract: We report on the development of highly efficient organic light-emitting diodes (OLEDs) utilized by balancing the energy transfer between multiple dopants, that is, multiple emissions from the multiple dopants were realized by balanced distributed energy transfer. From the cosensitizing fluorescent OLEDs, the peak external quantum efficiency (EQE) of 4.8% at 130 cd/m2 is demonstrated, which realized theoretical limits of ∼5.0% and means that nearly 100% of the singlet excitons are radiative. Also, the optimized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…For improving the operation properties of the optoelectronic devices, dye doping is an important and facile method [2,[4][5][6]. Resonance energy transfer is a well known phenomenon for organic semiconductor composite films containing donor and acceptor molecules.…”
Section: Introductionmentioning
confidence: 99%
“…For improving the operation properties of the optoelectronic devices, dye doping is an important and facile method [2,[4][5][6]. Resonance energy transfer is a well known phenomenon for organic semiconductor composite films containing donor and acceptor molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant literature (AlSalhi et al 2011;Chen and Hwang 2007;Kamtekar et al 2010;Lambeth 2004;Lee et al 2014;Lin 2009;Liu et al 2006;Madhava Rao et al 2013;Park et al 2009;Sebastian et al 2009;Segal et al 2007;So et al 2007;Sun et al 2014;Zink et al 2014) was referred to, and four experts were consulted, to verify the above research fronts. Among the research fronts mentioned above, six derived from bibliographic coupling are identified as important.…”
Section: Comparisonsmentioning
confidence: 99%
“…Samples were gently grounded, and deposited in a sample holder. 1 H NMR and 13 C NMR spectra were obtained on a Varian Unit Inova 400 MHz spectrometer. UV-Vis measurements were recorded on a JASCO V-570 spectrophotometer.…”
Section: Characterizationmentioning
confidence: 99%
“…Tris(8-hydroxyquinoline)aluminum (AlQ 3 ), amongst the most efficient electroluminescent materials, is widely used in organic light emitting diodes (OLED) as an electron-transport layer or a green emitter [1][2][3]. AlQ 3 is layered with hole transport materials between anode and cathode layers, and can be applied in flat panel or flexible displays by wide-range film deposition [4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%